Apoptotic potential of glucomoringin isothiocyanate (GMG-ITC) isolated from Moringa oleifera Lam seeds on human prostate cancer cells (PC-3) - Abd Karim, Nurul Ashikin; Adam, Aziza Hussein Bakheit; Jaafaru, Mohammed Sani; Rukayadi, Yaya; Abdull Razis, Ahmad Faizal (Multidisciplinary Digital Publishing Institute, 2023)
Inhibition of several protein pathways involved in cancer cell regulation is a necessary key in the discovery of cancer chemotherapy. Moringa oleifera Lam is often used in traditional medicine for the treatment of various illnesses. The plant contains glucomoringin isothiocyanate (GMG-ITC) with therapeutic potential against various cancer cells. Therefore, GMG-ITC was evaluated for its cytotoxicity against the PC-3 prostate cancer cell line and its potential to induce apoptosis. GMG-ITC inhibited cell proliferation in the PC-3 cell line with IC50 value 3.5 µg/mL. Morphological changes as a result of GMG-ITC-induced apoptosis showed chromatin condensation, nuclear fragmentation, and membrane blebbing. Additionally, Annexin V assay showed proportion of cells in early and late apoptosis upon exposure to GMG-ITC in a time-dependent manner. Moreover, GMG-ITC induced a time-dependent G2/M phase arrest, with reduction of 39.1 in the PC-3 cell line. GMG-ITC also activates apoptotic genes including caspase, tumor suppressor gene (p53), Akt/MAPK, and Bax of the proapoptotic Bcl family. Early apoptosis proteins (JNK, Bad, Bcl2, and p53) were significantly upregulated upon GMG-ITC treatment. It is concluded that apoptosis induction was observed in PC-3 cells treated with GMG-ITC. These phenomena suggest that GMG-ITC from M. oleifera seeds could be useful as a future cytotoxic agent against prostate cancer.